Creative Thinking Of Students In Primary Education And Methods Of Its Display In The Educational Process - Orolboy Kulmominov (Euro Asian Journal Publishing, 2024)
This article discusses in detail the ways of developing students' creativity in primary grades, and the methods of developing it in the personality of the student.
Keywords: Primary education; lesson; method; integration